PELAKSANAAN PEMBERIAN HARTA PENCAHARIAN KEPADA ANAK KEMENAKAN MENURUT HUKUM ADAT SUKU PALIANG DI DESA PASAR BARU KECAMATAN PANGEAN - Merigo, Tri Ipo; Jayakusuma, Zulfikar; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The existence of customary law in the community is a reflection of the life of the community and in each region has a different customary law in accordance with the customs that exist in the area with characteristics not written or codified. Likewise the customs in Pangean, have special characteristics and are different from customs in other Regions. The difference is in the distribution of inheritance which often triggers conflict in the family, especially on the name of the nephew in the list of beneficiaries inherited from the parents' livelihood. Therefore, the formulation of the problem of this thesis writing is: First, how is the distribution of livelihood assets to nephew children according to the customary law of the Paliang tribe in Pasar Baru Village, Pangean District? Second, how is the protection of children's inheritance rights over the distribution of livelihood to nephew children in the Paliang tribe in Pasar Baru Village, Pangean District?This type of research can be classified as empirical or sociological legal research, because in this study the writer directly conducts research at the location or place of study in order to provide a complete and clear picture of the problem under study. This research was conducted in Pasar Baru Village, Pangean District. Sources of data used, namely: primary data, secondary data and tertiary data. Data collection techniques in this study were interviews and literature review.The conclusions from the results of the study, first, the Law of Islamic Inheritance in perfect quality already applies in the Paliang tribe but in terms of quantity has not been evenly distributed across all Muslims. The parties who receive the inheritance in the Paliang indigenous tribe are biological children, wives and nephews. The method of ownership of inheritance in the Paliang tribal tribe is determined by the ulema of the ulama and customary stakeholders. Second, the protection of children's inheritance rights over the distribution of livelihoods is not realized and achieved. Because the Paliang tribe mentioned referring to Islamic law if it was not in accordance with Islamic law, it was not customary, but in Pasar Baru Village, ruled out Islamic law, so that the inheritance rights of children towards the distribution of livelihoods were simply ignored. This means that the division of livelihoods in the Paliang tribe is not in accordance with applicable regulations, and of course a prolonged conflict will occur. In addition, the customary provisions, namely as a child, get a 2/3 portion of all inheritance assets and the nephew gets a 1/3 portion of the total inheritance causing no legal protection of the inheritance rights of children. The author's suggestion is that it is expected that the ulama and traditional leaders can realize the function and existence of each so that the community can truly understand the Islamic knowledge contained in the distribution of inheritance to the treasure of search in the Paliang Tribe and can be practiced in daily life by the community.Keywords: Distribution of Livelihoods - Paliang Tribe - Pasar Baru Village, Pangean District